Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s13197-011-0378-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variety on the quality of tomato stored under ambient conditions

Abstract: Three processing and six fresh market tomato varieties harvested at "mature green" stage were evaluated for changes in quality. The total soluble solid, titratable acidity, sugar-acid ratio, pH, ascorbic acid content, colour and firmness were assessed. The storage room air temperature and relative humidity varied from 15.4(○)C to 16.2(○)C and 34.8% to 52.4%, respectively. At harvest, Marglobe Improved had better chemical quality characteristics compared with the other five fresh market varieties while towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
118
4
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 36 publications
28
118
4
6
Order By: Relevance
“…On the other hand, the ascorbic acid content of pink tomatoes decreased during the storage period. Similar results were reported by Tigist et al (2011) who found that a general trend of increase in ascorbic acid content, followed by a fall during the full ripening stage.…”
Section: Ascorbic Acidsupporting
confidence: 90%
“…On the other hand, the ascorbic acid content of pink tomatoes decreased during the storage period. Similar results were reported by Tigist et al (2011) who found that a general trend of increase in ascorbic acid content, followed by a fall during the full ripening stage.…”
Section: Ascorbic Acidsupporting
confidence: 90%
“…Data was analyzed with the Statistical Analysis System (SAS Institute Inc., Cary, NC). Comparisons between the sample means were done using the least significant differences (USD) at 5 % significance level (Workneh et al 2011c and2011d;Tigist et al 2011;Awole et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among the chemical properties, total soluble solids (TSS), dry matter (DM), pH, total titratable acidity (TA) and ascorbic acid (AA) were measured according to INIBAP technical guidelines (Dadzie and Orchard 1997;Workneh et al 2011a and2011b;Tigist et al 2011;Awole et al 2011;Kundan et al 2011). TSS was measured by blending 30 g of pulp tissue that was taken from the transverse section of the fruit in 90 m1 distilled water for 2 min in a blender (6001x Model No.…”
Section: Chemical Analysismentioning
confidence: 99%
“…These results are consisted with those reported by Wang et al (2008) and Tigist, Workneh and Woldetsadik (2013) who observed a general trend of increase in ascorbic acid content of pink tomatoes, followed by a decline during the full ripening stage. Once tomatoes were not harvested in full ripening stage, the increase in ascorbic acid content is in accordance with the increase in other parameters associated with ripening , such as lycopene.…”
Section: Resultssupporting
confidence: 91%